2021
DOI: 10.21203/rs.3.rs-427022/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and Power Dissipation Consideration of PFAL CMOS v/s Conventional CMOS based 2:1 Multiplexer and Full Adder

Abstract: Increasing transistor switching time and rising count of transistors integrated over a chip area has given a high pace in computing systems by several orders of magnitude. With the integration of circuits, number of gates and transistors are increasing per chip area. CMOS Logic family is preferred due to its performance and impeccable noise margins over other families. However with integration in every digital circuit, the energy due to switching of gate doesn’t decrease at same rate as gates are increased per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In a study by Zean et al [3], they showed that CNTFETbased inverters showed a significant decrease in PDP as compared to silicon-based. This is further supported by research conducted by Aara et al [4] which highlighted the possible reduction in power consumption by 6.30% in a 2:1 MUX application using CNTFET. CNT material used in designing the Analog to Digital Converter (ADC) [5] also has been studied.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In a study by Zean et al [3], they showed that CNTFETbased inverters showed a significant decrease in PDP as compared to silicon-based. This is further supported by research conducted by Aara et al [4] which highlighted the possible reduction in power consumption by 6.30% in a 2:1 MUX application using CNTFET. CNT material used in designing the Analog to Digital Converter (ADC) [5] also has been studied.…”
Section: Introductionsupporting
confidence: 64%
“…The outcome served as the guideline for researchers and experimentalists designing low-power circuits for future electronic device applications. Therefore, this paper simulates and characterizes the CNTFET-based 2:1 MUX application using the established SPICE model simulated in HSPICE extended those from reference [3], [4], and [7]. The electrical performance evaluated is the propagation delay, average power consumption, PDP, and EDP comparing design approaches which are conventional CMOS, PTL, and GDI approaches.…”
Section: Introductionmentioning
confidence: 99%